GAMBARAN TINGKAT KEPUASAN PASIEN TERHADAP KOMUNIKASI PETUGAS REKAM MEDIS DI TEMPAT PENERIMAAN PASIEN RAWAT JALAN (TPPRJ) RSUD Dr. M. ZEIN PAINAN - Rahmadhani Rahmadhani; Oktamianiza Oktamianiza; Heru Rahmat Wibawa Putra; Siti Handam Dewi; Putri Indah Maharani (Ensiklopedia of Journal, 2026)
Patient satisfaction is an indicator of the quality of health services, which is assessed by service performance. At Dr. Hospital. M. Zein Painan, there are patients who are dissatisfied with outpatient registration services. This study aims to assess patient satisfaction with staff communication at the outpatient reception area (TPPRJ) using the 5-dimensional Servqual method. This research is quantitative research with a descriptive approach carried out at RSUD Dr. M. Zein Painan on 29 May-03 June 2024, with a population of 10,000 outpatients in January and a sample of 99 patients selected using accidental sampling technique; Data collection was carried out through questionnaires and questionnaires, processed using editing, coding, processing and cleaning techniques, and analyzed using univariate analysis. Based on the results of the analysis on each dimension, it can be seen that of the 99 respondents, in the reliability dimension the majority expressed satisfaction 56.6%, responsiveness the majority expressed satisfaction 54.5%, assurance the majority expressed satisfaction 57.6%, empathy the majority expressed satisfaction 54.5%, tengibles the majority expressed satisfaction 60.6% expressed satisfaction and communication officers mostly expressed satisfaction 57.6%. The conclusion of this study was that the level of patient satisfaction was that some of them were less satisfied with the responsiveness dimension (45.5%) and the empathy dimension (45.5%). The suggestion is that the hospital coordinate with quality management regarding all dimensions of patient satisfaction to improve service quality.Keywords: Patient Satisfaction, Service Quality, Registration, Outpatient